Double-loculated Calcification Chronic Subdural Hematoma: Case Report and Literature Review. Issue 2 (May 2015) - Li, Xinwei; Wan, Yingfeng; Qian, Cong; Yang, Shuxu; Zhu, Xianli; Wang, Yirong
Abstract : Calcified chronic subdural hematoma (CCSDH) is a rare pathologic entity and, until recently, has been only published as case reports. We first present a patient with a double-loculated CCSDH who obtained good reexpansion after craniotomy to remove the thick calcified inner membrane and hematoma. In addition, we reviewed 46 cases in literature and conducted a summary about the incidence, clinical characteristics, radiologic findings, and therapeutic strategies of CCSDH. Surgical treatment for CCDSH with a sudden neurological deterioration is feasible and often results in neurological improvement; however, a crucial consideration was required in asymptomatic CCSDH. It is expected that CCSDH will be rarer in the future.